A method for constructing an optimal control strategy in a linear terminal problem - Kastsiukevich, Dzmitry A.; Dmitruk, Natalia M. (Journal of the Belarusian State University. Mathematics and Informatics, 2021)
This paper deals with an optimal control problem for a linear discrete system subject to unknown bounded disturbances, where the control goal is to steer the system with guarantees into a given terminal set while minimising the terminal cost function. We define an optimal control strategy which takes into account the state of the system at one future time instant and propose an efficient numerical method for its construction. The results of numerical experiments show an improvement in performance under the optimal control strategy in comparison to the optimal open-loop worst-case control while maintaining comparable computation times.